Genetic variants within obesity-related genes are associated with tumor recurrence in patients with stages II/III colon cancer. Issue 1 (January 2015) - Sebio, Ana; Gerger, Armin; Matsusaka, Satoshi; Yang, Dongyun; Zhang, Wu; Stremitzer, Stefan; Stintzing, Sebastian; Sunakawa, Yu; Yamauchi, Shinichi; Ning, Yan; Fujimoto, Yoshiya; Ueno, Masashi; et al.
Abstract : Objective: Obesity is an established risk factor for colorectal cancer (CRC) incidence and it is also linked to CRC recurrence and survival. Polymorphisms located in obesity-related genes are associated with an increased risk of developing several cancer types including CRC. We evaluated whether single-nucleotide polymorphisms in obesity-related genes may predict tumor recurrence in colon cancer patients. Materials and methods: Genotypes were obtained from germline DNA from 207 patients with stage II or III colon cancer at the Norris Comprehensive Cancer Center. Nine polymorphisms in eight obesity-related genes ( PPAR, LEP, NFKB, CD36, DRG1, NGAL, REGIA, and DSCR1 ) were evaluated. The primary endpoint of the study was the 3-year recurrence rate. Positive associations were also tested in an independent Japanese cohort of 350 stage III CRC patients. Results: In univariate analysis, for PPARrs1801282, patients with a CC genotype had significantly lower recurrence probability (29±4% SE) compared with patients with a CG genotype (48±8% SE) [hazard ratio (HR): 1.77; 95% confidence interval (CI), 1.01–3.10; P =0.040]. For DSCR1rs6517239, patients with an AA genotype had higher recurrence probability than patients carrying at least one allele G (37±4% SE vs. 15±6% SE) (HR: 0.51; 95% CI, 0.27–0.94; P =0.027). This association was stronger in the patients bearing a left-sided tumor (HR: 0.34; 95% CI, 0.13–0.88; P =0.018). In the Japanese cohort, no associations were found. Conclusion: This hypothesis-generating study suggests a potential influence of polymorphisms within obesity-related genes in the recurrence probability of colon cancer. These interesting results should be evaluated further. Abstract : Supplemental Digital Content is available in the text.